Does acute fatigue affect player load during an agility task? - Marques, J. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Accelerometers have been used to quantify deceleration (Nedergaard et al., 2014) and may be useful for monitoring neuromuscular fatigue (Buchheit et al., 2015). Whether they can be used to quantify fatigue-induced changes in loading during reactive agility tasks is unknown. Therefore, the aim of this study was to examine the differences in loading during an agility test (AT) before and after an acute bout of fatigue (AFT). Methods: Seven male trained soccer players (mean±SD age: 26.1±5y, weight: 72±8kg, height: 174±7cm) were fitted with 100Hz integrated tri-axial accelerometers (Catapult S5, Catapult innovations, Canberra) at the scapulae (SCAP) and right (R) and left (L) ankle. Following a standardized warm-up participants performed a 20m maximal sprint and upon hearing an audio signal would decelerate, change direction (180°) and return to the start line. The audio signal was randomly provided at 1.0, 1.5 and 2.0s with players performing 2 repetitions for each time condition both pre- and post-AFT (12 in total). The AFT consisted of maximal 25m (2x12.5m) shuttle sprints interspersed with 20s rest. The test was ceased when a 5% decrement in sprint performance was reached. Load was measured using the player load variable (PL) and its tri-axial components. Repeated measures ANOVA was used to compare temporal differences across the AFT and the magnitude of the effects (ES) was calculated. A paired-sample t-test was conducted to examine differences in stride variables (e.g. number of steps and distance covered) between pre- and post-fatigue. Results: A 5% sprint decrement (p<0.01, ES: -2.5) corresponded to average decrease in PL of 19.9, 23.3, and 17.3% (p<0.01, ES: 1.4-2.34) for SCAP, R and L. The AFT did not have a statistically significant effect on PL (p>0.05) during any of the agility tests (ES: trivial to small in all unit locations, 0.1-0.4). The vertical component of PL was 5 times higher at the ankles compared to SCAP. No changes were observed for stride variables (p>0.05). Discussion: A 5% reduction in sprint performance was associated with a 4-fold larger reduction in PL, possibly due to reduced vertical stiffness (Girard et al., 2011). Our findings may support the use of accelerometers to monitor fatigue as well as quantifying player load during agility tasks. The use of accelerometers may also provide practical insight into the changes experienced during agility tasks.